Blanket Peat Restoration: Numerical Study of the Underlying Processes Delivering Natural Flood Management Benefits. Issue 4 (26th April 2021) - Goudarzi, Salim; Milledge, David G.; Holden, Joseph; Evans, Martin G.; Allott, Timothy E. H.; Shuttleworth, Emma L.; Pilkington, Michael; Walker, Jonathan
Abstract: Restoration of eroded blanket peatlands through revegetation and gully blocking is observed to also deliver significant natural flood management (NFM) benefits (reduce and delay floodpeaks). But there is a lack of clear understanding regarding how different catchment processes interact/counteract under each intervention scenario. We seek to provide more insight by rigorously calibrating TOPMODEL rainfall‐runoff model to different experimental catchments each representing an intervention scenario. Through numerical experimentation with the calibrated parameters, we estimate the impact‐magnitude of different processes. Our findings confirm the NFM benefits of these restoration‐focused interventions. In both interventions and in our largest storms, both the delay and reduced floodpeaks are primarily due to surface roughness reducing the floodwave speed thus thickening the overland flow; we conceptualize this as an increase in a "kinematic storage." Impact of gully blocking in increasing kinematic storage is very significant and comparable to that of revegetation alone. Interventions' impact on "static storage" (interception + ponding + evapotranspiration) becomes important for smaller storms. Although interventions always increase lag times, they can be less effective in reducing peak magnitude when maximum rainfall intensity is sustained for durations longer than mean catchment delay. We propose two approaches to further increase catchment's static and kinematic storage. Finally, while our field‐scale numerical study contributes to the evidence‐base for NFM's effectiveness, it also provides a basis for modeling these interventions in the future. Such catchment‐scale numerical studies are necessary to extend our findings to spatial scales where flooding can cause socioeconomic damage, and to provide a tool for optimizing the distributed configuration of these interventions. Key Points: Blanket peat restoration interventions significantly reduce flood risk to the downstream communities at risk Revegetation and gully blocking of eroded blanket peat reduces flood risk primarily through increased surface roughness and not storage Impact of gully blocking in reducing increasing "kinematic" surface storage is very significant and equivalent to revegetation alone